Demographic Associations of Low Back Pain; A Case Control Study: Demographic Association of Low Back Pain - Khokhar, Samia Khalid; Qamar, Aisha; Surti, Ambreen; Fahim, Muhammad Faisal; Mahar, Yasmeen (Pakistan Journal of Health Sciences, 2022)
Low back pain is a condition of prime concern by World Health Organization. It affects the quality of life and execution of work at jobs worldwide. Among these 90% cases are categorized as non-specific low back pain. Objectives: To evaluate demographic characteristics of cases of low back pain (LBP). To compare the BMI between cases and control groups in relation to low back pain. Methods: This case control study was undertaken on 178 subjects, comprising of equal number of cases of LBP and healthy controls with age ranging from 18-65 year, enrolled by non-probability convenience sampling at PNS Shifa Hospital, Karachi after obtaining ethical approval from ERC of BUHSC. Demographic parameters like gender, age, marital status, and occupation were noted on pre-designed proforma and compared between cases and controls. Body mass index (BMI) was also compared between the groups. Results: The study showed LBP as more common in women, with significant association with marital status, occupation and BMI. The participants were divided into 5 groups according to age, maximum 29.8%, participants were in age group 36-45 years followed by 24.7% in 26 -30 years, 20.2% in 46 -55 years, 16.95 in 18 -25 years and only 8.4% in 56-65 years. Most of the cases were housewives followed by office workers. A highly significant result was seen when BMI was compared between cases and control as most of the cases (41.6%) were overweight as compared to controls. Conclusion: The incidence of LBP was more among women, married, housewives and overweight subjects